Blockchain and Islamic Finance: Innovating Within Tradition - Mochamad Dandi (Journal of Islamic Economic Insights, 2025)
The financial sector is at a crossroads, merging emerging technologies with the traditional principles of Islamic finance governed by Shariah law. This study examines the integration of blockchain technology to bolster transparency, security, and efficiency in Islamic financial systems while upholding Shariah compliance. Through a comprehensive literature review of reputable sources such as Emerald and IEEE Xplore, our findings highlight blockchain's potential to streamline Shariah-compliant processes, enhance financial inclusion, and drive innovation, addressing key challenges faced by the industry.